Profile of intravenous glyburide for the prevention of cerebral edema following large hemispheric infarction: evidence to date - King ZA; Sheth KN; Kimberly WT; Simard JM (Dove Medical Press, 2018)
Zachary A King,1 Kevin N Sheth,1 W Taylor Kimberly,2 J Marc Simard3 1Department of Neurology, Division of Neurocritical Care and Emergency Neurology, Yale University School of Medicine, New Haven, CT, USA; 2Department of Neurology, Division of Neurocritical Care and Emergency Neurology, Massachusetts General Hospital, Boston, MA, USA; 3Department of Neurosurgery, University of Maryland School of Medicine, Baltimore, MD, USA Abstract: Glyburide (also known as glibenclamide) is a second-generation sulfonylurea drug that inhibits sulfonylurea receptor 1 (Sur1) at nanomolar concentrations. Long used to target KATP (Sur1–Kir6.2) channels for the treatment of diabetes mellitus type 2, glyburide was recently repurposed to target Sur1–transient receptor potential melastatin 4 (Trpm4) channels in acute central nervous system injury. Discovered nearly two decades ago, SUR1–TRPM4 has emerged as a critical target in stroke, specifically in large hemispheric infarction, which is characterized by edema formation and life-threatening brain swelling. Following ischemia, SUR1–TRPM4 channels are transcriptionally upregulated in all cells of the neurovascular unit, including neurons, astrocytes, microglia, oligodendrocytes and microvascular endothelial cells. Work by several independent laboratories has linked SUR1–TRPM4 to edema formation, with blockade by glyburide reducing brain swelling and death in preclinical models. Recent work showed that, following ischemia, SUR1–TRPM4 co-assembles with aquaporin-4 to mediate cellular swelling of astrocytes, which contributes to brain swelling. Additionally, recent work linked SUR1–TRPM4 to secretion of matrix metalloproteinase-9 (MMP-9) induced by recombinant tissue plasminogen activator in activated brain endothelial cells, with blockade of SUR1–TRPM4 by glyburide reducing MMP-9 and hemorrhagic transformation in preclinical models with recombinant tissue plasminogen activator. The recently completed GAMES (Glyburide Advantage in Malignant Edema and Stroke) clinical trials on patients with large hemispheric infarctions treated with intravenous glyburide (RP-1127) revealed promising findings with regard to brain swelling (midline shift), MMP-9, functional outcomes and mortality. Here, we review key elements of the basic science, preclinical experiments and clinical studies, both retrospective and prospective, on glyburide in focal cerebral ischemia and stroke. Keywords: glyburide, sulfonylurea receptor 1, stroke, cerebral ischemia, brain swelling, malignant edema, matrix metalloproteinase-9